THE INFLUENCE OF COMPETENCE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE PT. YOROZU AUTOMOTIVE INDONESIA - Nika Yulianisa; Aji Tuhagana; Zenita Apriani (PT. Berkah Digital Teknologi, 2024)
Purpose: The purpose of this study was to determine the effect of competence and work motivation on employee performance. Research Methodology: This study used a quantitative approach through multiple linear regression analysis and data processing was carried out using SPSS27. The primary data source was obtained by distributing questionnaires to employees of PT Yorozu Automotive Indonesia. The population was 176 employees, with a sample size of 64 employees calculated using the Slovin formula. Results: The results obtained are that there is no partial influence of competence on the performance of employees of PT. Yorozu Automotive Indonesia with a value of 1,284 and a significant level of 0.001. However, there is a partial influence of work motivation on the performance of employees of PT. Yorozu Automotive Indonesia with a value of 7,965 and a significant level of 0.001. Additionally, there is a simultaneous influence between the variables Competence (X1) and Work Motivation (X2) on Employee Performance (Y) with a value of 108,081 and a sig level of 0.001. Limitations: The study is limited to a specific company, PT Yorozu Automotive Indonesia, and the sample size may not be representative of the entire population. Contribution: The findings of this study contribute to the understanding of the importance of work motivation in enhancing employee performance, especially in the context of the automotive industry.